A Human Resource Development Program for Information Technology Engineers using Project-Based Learning - Nakayama, Minoru; Fueki, Manabu; Seki, Shinji; Uehara, Toshikazu; Matsumoto, Kenji (International Journal of Advanced Corporate Learning (iJAC), 2012)
This paper reports the case of an educational practice and evaluation of team learning using project-based learning to develop Information Technology engineers. This program aims to develop the competencies of engineers, such as their communication skills, problem solving within teams, and other abilities. Its subject is the â??Upper Processâ? of Information Technology systems development. To determine the feasibility of the course, it was conducted at a computer college. The teamâ??s products and team learning activities were evaluated using rubrics and self evaluation inventories, and learning performance was discussed. Also, the evaluation of the learning management system affected the learning activity.